Granja-Escuela "El Encinar" - Gutiérrez Sánchez , Marta (Educación y Futuro: Revista de Investigación Aplicada y Experiencias Educativas, 2001)
With a very living and personal style the author of this article describes the educational work performed at the farm-school "El Encinar". It is shown as an experience and a resource in non-formal environmental education within a natural means. where the Salesian spirit is present in the whole project.